Command based line following robot using RF technology - Bhatti, Anjun; Bhatti, Mohammad; Khowaja, Kamaran; Shah, Asadullah (Springer New York LLC, 2011)
This research paper demonstrates a prototype development of an Intelligent Command Based Line Follower Robot (LFR) using Radio Frequency (RF) Technology. Mostly the LFR are build by using microcontroller chips. One of the basic and most fundamental problems with LFR based upon microcontroller chips is that they are preprogrammed. Due to these preprogramming limitations LFR cannot accept any instruction and command in real time from outside users other than what is already fixed. The proposed prototype systems is designed and demonstrated to recognize, understand and modify the actual performance and the movements of the robot following the path by getting information in real time from three Light Dependent Resistor (LDR) sensors via Parallel Port Interface Circuit (PPIC) connected to PC. A computer program is implemented in C-language to accept user commands and also control the robot autonomously according to the received signals.